2021
DOI: 10.1108/ijmhsc-04-2020-0040
|View full text |Cite
|
Sign up to set email alerts
|

Health-seeking behaviour and practices among immigrant retail traders in an urban setting in North-Western Ghana

Abstract: Purpose This study aims to investigate the health-care-seeking behaviour and practices of West African migrants who reside and operate in Wa, Ghana, as itinerant retailers. Design/methodology/approach The study was cross-sectional and used the quantitative research approach. The analysis was done on a target population comprising 122 itinerant immigrant retail traders in Wa, Ghana. Fisher’s exact test and logistic regression were used to analyse the data. Findings Malaria was the commonest disease among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Similar dimensions on the risks of informal itinerant trading were observed by Ref. [ 18 ], and [ 38 ]. They found that many itinerant immigrant traders considered informal retail trade as an uncertain and risky business venture.…”
Section: Conceptual and Theoretical Perspectivessupporting
confidence: 83%
See 2 more Smart Citations
“…Similar dimensions on the risks of informal itinerant trading were observed by Ref. [ 18 ], and [ 38 ]. They found that many itinerant immigrant traders considered informal retail trade as an uncertain and risky business venture.…”
Section: Conceptual and Theoretical Perspectivessupporting
confidence: 83%
“…They found that many itinerant immigrant traders considered informal retail trade as an uncertain and risky business venture. Hence, many immigrant entrepreneurs regard itinerant retail trade as a tiring work and a necessity [ 18 , 39 ]. In relation to the working conditions of immigrant entrepreneurs [ 1 , 22 , [40] , [41] , [42] ], and [ 43 ] maintained that it is a function of both the physical and business policy environment in which they operate.…”
Section: Conceptual and Theoretical Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Yendaw and Tampah-Naah (2021) and Turner and Oswin (2015), itinerant retailing of wares is a common source of livelihood for many people in many developing countries, and it is principally undertaken in urban areas with a huge customer base. The term 'itinerant immigrant trader/retailer' has been used in this study to include a wide range of immigrant retailers who transact their retail trades outside the formal arrangements of business operations instituted by the state (Yendaw et al, 2019;Harris, 2009;Hart, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale intra-African migration (especially for itinerant immigrants) in the sub-Saharan African region has only elicited scientific research interest in terms of understanding business practices, health-seeking behaviour, points of entry and business strategies (Yendaw et al, 2019;2021;Yendaw & Tampah-Naah, 2021). Berriane's (2018) work in Morocco which focused on itinerant immigrants revealed them to be temporary settlers seeking to transition to Europe but failed to discuss their residential choices.…”
mentioning
confidence: 99%